An Attribute of Social Security among Farmers in India - Kaswa, Divya (Research Parks Publishers, 2023)
India's economy is heavily dependent on agriculture, both in terms of the employment it creates and its contribution to GDP. A recent economic assessment voiced worry about the declining contribution of capital formation from the agricultural sector to GDP. A research titled